Social media affordances in music learning and performance: a systematic review of empirical evidence, 2020–2026 - Benovan Rahmandicca; Ardipal Ardipal; Tulus Handra Kadir; Indrayuda Indrayuda (Journal of Educational and Learning Studies, 2026)
Social media platforms have become embedded in how musicians practise, perform, and are taught, yet the research base describing this phenomenon remains fragmented across disciplines, platforms, and educational levels. This systematic literature review examined how social media shapes music learning and performance, synthesising evidence on informal self-directed learning, formal instructional integration, teacher professional communities, and the psychosocial consequences of platform-mediated visibility. Following the PRISMA 2020 framework, a search was executed in the Scopus database on 24 July 2026, returning 657 records; after removing one duplicate, 656 records were screened by title, abstract, and keyword, of which 249 were assessed in full text against explicit eligibility criteria requiring a substantive combination of music, a named social media platform, and a learning or performance focus. Fifty studies published between 2020 and 2026 met the inclusion criteria and were retained for synthesis. Findings converged on four themes: social media, particularly YouTube, Instagram, and WeChat, functions as an informal and self-regulated learning resource that complements rather than replaces formal instruction; platforms are increasingly integrated into formal curricula and teacher professional communities as tools for content curation, feedback, and community-building; the visibility and metrics inherent to platforms generate documented risks of social comparison, performance anxiety, and impostor phenomena among students and educators; and a smaller critical literature questions the platformization of musical labour and pedagogy itself. Theoretically, the review extends self-regulated learning and communities-of-practice frameworks into networked, platform-mediated contexts. Practically, findings suggest that music educators can deliberately scaffold platform use to support motivation while mitigating comparison-related harms. Future research should pursue longitudinal designs, cross-platform comparisons, and greater representation from under-studied regions and non-Western musical traditions